Beyond the usual suspects: using political science to enhance public health policy making. Issue 11 (25th February 2015) - Fafard, Patrick
Abstract : That public health policy and practice should be evidence based is a seemingly uncontroversial claim. Yet governments and citizens routinely reject the best available evidence and prefer policies that reflect other considerations and concerns. The most common explanations of this paradox emphasise scientific disagreement, the power of 'politics', or the belief that scientists and policymakers live in two separate communities that do not communicate. However, another explanation may lie in the limits of the very notion of evidence-based policy making. In fact, the social science discipline of political science offers a rich body of theory and empirical evidence to explain the apparent gap between evidence and policy. This essay introduces this literature with a particular emphasis on a recent book by Katherine Smith, Beyond evidence-based policy in public health: the interplay of ideas . As the title suggests, Smith argues that what matters for public health policy is less scientific evidence and much more a more complex set of ideas. Based on detailed case studies of UK tobacco and health inequality policy, Smith offers a richly textured alternative account of what matters for policy making. This excellent book is part of a small but growing body of political science research on public health policy that draws on contemporary theories of policy change and governance more generally. This essay provides a window on this research, describes some examples, but emphasises that public health scholars and practitioners too often retain a narrow if not naive view of the policy-making process.